Administration of the Health and Hospitals Fund : Department of Health and Ageing - Australian National Audit Office (Barton, ACT : Australian National Audit Office, 2012)
The audit objective was to assess the effectiveness of DoHA's administration in supporting the creation and development of health infrastructure from the HHF, including DoHA's support for the Health Minister and the HHF Advisory Board.
"Audit Team: Sue Sheridan, Denis Preston, Elizabeth Cusack, Edward Macgregor, Lesley Jackman, Andrew Morris, Tom Ioannou."--p. 4.
Includes bibliographical references and index.
Also freely available online. On 3/07/12 available from the website of the Australian National Audit Office at
Also available online
Keywords: Health and Hospitals Fund (Australia) -- Auditing; Australia. -- Department of Health and Ageing -- Auditing; Hospitals -- Australia -- Auditing; Public health -- Australia -- Auditing; Australian